Lateral torsional buckling of thin-walled rectangular and I-section laminated composite beams with arbitrary layups - Halim, Abdul Halim (Kansas State University, 2020)
Structural elements made of fibrous composites are increasingly used in aerospace, automotive, civil and marine structures due to their high stiffness/strength-to-weight ratio and corrosion resistance properties. Most of the composite structural elements are thin-walled and their design is often controlled by stability considerations mainly due to slenderness effects. Hence, for thin-walled slender composite beams, lateral torsional buckling (LTB) is the dominant failure mode regardless of the fiber orientations. In this study, closed form analytical solutions for generally anisotropic (arbitrary layup) thin-walled rectangular-section cantilever and I-shape beams under pure bending are presented. Corresponding differential equations are formulated using the kinematics, constitutive and equilibrium equations for the beams and solved using infinite series approach. Restrained warping is also considered in the formulation for I-section beam. A parametric study is performed to investigate the effects of beam length to depth ratio (l/h) and flange and web thickness effects on the critical buckling load. Good agreement between analytical solution and finite element results was obtained for both section types. The solution is also validated against Timoshenko’s classical buckling solution for isotropic beam for both rectangular and I-sections and a perfect match was observed. Analytical solutions could be adapted for rectangular or I-section beams subjected to various loading and boundary conditions. The solution is equally applicable for hybrid thin-walled laminated beams for the given sections. Some experiments on basic orthotropic beams are also conducted.
Keywords: Lateral torsional buckling; Infinite series; Composite beam; Thin-walled; Anisotropic I-beam; Arbitrary layups